SERVICE QUALITY AND ORGANISATIONAL PERFORMANCE IN THE HOSPITALITY INDUSTRY IN NIGERIA (World Economics and Finance Bulletin, 2022)
The study determined the relationship between service quality organisational performance the hospitality industry in Nigeria. The specific objectives of the study were: to examine the relationship between physical structure and organisational performance; to determine the relationship between employee behaviour and organisational performance of Nigeria based on the SERVQUAL Model. Primary source of data collection was adopted. Two hundred and twenty two questionnaires were administered to the guests in the selected hotels in Nigeria. Linear regression analysis was employed to test the hypotheses. The findings revealed that there is positive and significant relationship between physical structure and employee behaviour with organisational performance in in the hospitality industry in Nigeria. Conclusively, service quality enhances organisational performance through customer satisfaction and customer retention. It is recommended that hospitality management should renovate or reconstruct their building to meet the guests’ expectations; that hospitality management should discard old furniture and replace with modern furniture in order to create new outlook of the hotel, and that training and retraining of employee of hospitality firms be done intermittently so that responsiveness and empathy can be cultivated.Service Quality